ASEAN FTAS DAN LIBERALISASI PERDAGANGAN JASA : TANTANGAN JASA TENAGA KERJA BAGI INDONESIA - Tri Nuke Pudjiastuti (Pusat Penelitian Politik, 2010)
Under contemporary globalization and liberalization particularly with many kinds ofFree Trade Agreements FTAs in terms of liberalization of services and labours Indonesia has to deal with so many challenges In one side theforeign labour mobility will increase in thefuture ofIndonesian labour market while lack of competency mostly for local or domestic labours In another side at the current situation Indonesian migrant workers are stilldominated by unskilled workers which is notpart of trade ofservices in FTAs scheme